VISUALISASI BURUH BANGUNAN DALAM KARYA FOTOGRAFI EKSPRESI - Giantoro, Rahmat Putra; Raharjo, Anis; Pramana, I Made Bayu (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
study entitled visualization of construction workers in expression photography. The author realizes that the stigma of construction workers is still very attached to the community, this has made the promotion of construction workers as a visualization of construction workers in expression photography. The creation of this work aims to broaden students' knowledge of expression photography. Expression photography is a photographic work that is conceptualized with the chosen object and which is presented and presented for the benefit of the photographer with an overflow of his artistic expression, then the work can become a work of expression photography. In this case, the photographic work is interpreted as a medium of expression that displays the identity of the photographer in the process of creating artistic photographic works. His photographic work is more of a pure artistic work of photography (fine art photography) because the form of his appearance focuses on the expressive-aesthetic value of art itself. (Soedjono, 2006) In doing this photographic work, the author wants to change the public's view of construction workers and also change the stigma that exists in society, so that construction workers can be more valued and appreciated in any form. Why did the writer choose expression photography using the collage technique, because the author wanted to experiment with other shapes and objects and the author also wanted to develop himself as an artist in the field of photography with the aim of finding his identity.